Analysis of the Effects of Biomass Stabilization Under Varying Thermal Conditions with Respect to the Quality Characteristics of Compost Transformation Products - Mariusz Adamski; Marcin Herkowiak; Przemysław Marek; Kamila E. Klimek; Magdalena Kapłan (Energies)
The aim of this work was to analyze the influence of thermal conditions and the presence of biomass in the chamber on the composting process. The work analyzed the process of the aerobic decomposition of grass, the inoculating fraction and the structure-forming fraction. The analysis covered the batch composting process using veterinary biomass in the treatment chamber. Observations of the process included the following: determining the rate of mineralization, process temperatures, pH, process gas concentrations, chemical composition, physical properties of the compost, and the maturity of the compost. In all analyzed samples, the composting process works correctly in terms of thermal parameters; the obtained fresh compost, after the thermophilic phase has ended, requires action be taken with reference to the values of the seed generation index and the respiration activity (AT4) parameter. After the thermophilic phase, after 60 days of composting, it was noted that for P1 (Probe 1) and P2 (Probe 2) mixtures, the seed germination level decreased below 10%. The AT4 parameter for the P1 and P2 compost samples was between 29.8 and 26.2 mg O2∙g−1. The improvement of the germination level to values in the 30% to 40% range for the maturing compost samples was caused by the thermal conversion of biomass with the regulation of air and water conditions. The phytotoxicity of the compost was overcome, while an improvement in the value of the AT4 index was achieved.